The Development of Conductometric Biosensor for Determination of Uric Acid Concentration in Human Serum Using Screen Printed Carbon Electrode (SPCE) – Nata De Coco - Abdi Naufal Ramadhan; Luluil Maknun; Noerma Juli Azhari (ALCHEMY Jurnal Penelitian Kimia, 2015)
The control of uric acid is important. A high level of uric acid can cause gout disease. Therefore a simple, fast, and accurate method for uric acid determination is required. In this research a conductometric biosensor has been developed by SPCE – Nata de coco for uric acid determination. The prepared biosensor was optimized to get a good performance of biosensor and it is applicable for human serum samples. The optimized variables were enzyme concentration, membrane thickness and pH solution. The various enzyme concentration were 6 μg/mL; 12 μg/mL; 18μg/mL; 24 μg/mL. The various membrane thickness were 5 μm; 10 μm; 15 μm. Meanwhile, the various pH solution were 7; 7.5; 8; 8.5; 9. The optimum enzime concentration was 18 µg/mL with the membrane thickness and pH were 5 µm and 8, respectively. The prepared biosensor can determine the uric acid concentration at range of 0 – 1.2 ppm with the sensitivity of 7.74 µS/ppm and the limit detection is 0 ppm. The biosensor was applied to uric acid detection in human serum with accuracy of 95 %.